Blueprinting Teacher-Made Tests in EFL Classrooms: Challenges Faced by Junior High School Teachers - Wiwiek Wahyuni; Muhammad Nur Akbar Rasyid; Surya Dita (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Blueprinting, or a table of specifications, is essential in question preparation because it aligns test items with learning objectives, content coverage, cognitive levels, item formats, and scoring weight. In practice, however, it is still often treated as an administrative document rather than an assessment-design tool. This study analyzed English teachers’ difficulties in applying blueprinting to question preparation at SMP Negeri 1 Limboro, the factors contributing to these difficulties, and the strategies teachers used to overcome them. Using a descriptive qualitative design, data were collected from five English teachers through semi-structured interviews, observation, and document analysis of blueprint forms and teacher-made tests, and were analyzed thematically. The findings show that teachers’ difficulties centered on limited conceptual understanding of blueprinting, difficulty formulating measurable indicators, uncertainty in distributing cognitive levels, weak alignment between items and learning objectives, time constraints, and limited training or institutional support. To cope with these difficulties, teachers relied on peer discussion, adaptation of existing templates, online examples, and workshops. Overall, these difficulties point to a broader issue of teacher assessment literacy shaped by workload and school-level assessment culture. Practical training, collaborative item review, and simple blueprint templates are recommended to improve the quality of teacher-made questions.